Multiformity and Economic Importance of True Brachyuran Crabs - Rana, Saroj (Edelweiss Applied Science and Technology, 2018)
The brachyuran crabs are diversified and widely distributed habitant throughout the world, apart from Antarctica, they are reported from all the niches of network. They are dominant in all over estuaries and found in unfathomable depths of the Ocean down to 6000m and in the high mountains up to 3500 m above the sea level. Numerous species have evolved to lead terrestrial habitats. Mostly are in fresh water, and some of these crabs have evolved to survive as phytotelms, inside empty shells of the snails, within corals "symbiotically" or "commensally" and reported from alpine, caves and desert as well. Their sizes range from 2mm to 5.5mm the weight ranges from few milligrams up to 19 kg. The fishery of the spanner crab, (Ranina ranina) has been thriving since World War II. People use crabs to cure different diseases: stomachache liver and lungs diseases healing wound osteoporosis and epilepsy and reproductive malfunction in women. This review aimed to find diversity and economic importance of crabs, which resulted positive and negative approaches. The crabs are multi-useful with diversified habitats, sizes and utility. Hence, it is suggested that the government should incorporate this in health care system into the existing one to ensure proper development and binding ethno-medicine in Nepal.